REMEDIASI MISKONSEPSI PADA MATERI TEKANAN HIDROSTATIK MENGGUNAKAN MODEL CLIS BERBANTUAN REFUTATION TEXT - Uray Dessy Eka Putri; Stepanus Sahala Sitompul; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe research’s goal is to know the effect of CLIS model implementation by using the refutation text in remediating the student misconception in hydrostatic pressure topic in SMP Negeri 5 Pontianak. The pre-experimental design with the design of one group pretest-posttest was used in this research. The population is all 8th grade students of A, B, C, and D class of SMP Negeri 5 Pontianak. The learning sample was taken on an intact group of 8th D class with 30 students. The research instrument was using the diagnostic test that consists of 12 question of multiple questions and open question. The average declining percentage after the remediation by using the CLIS model with refutation text was 51,39%, with the highest declining happened on indicator 1 which was 63,33%. The Mc Necmar test was tested with the significance of 5% which shows that there was a significant changing of misconception after the CLIS with refutation text was applied to remediate the misconception. The CLIS model that utilizes the refutation text is effective to remediate the misconception of students in hydrostatic pressure topic or material with the DQM score of 63,19% which is considered as medium. Keywords: Remediation, Misconception, CLIS, Refutation Text, Hydrostatic Pressure